Exploring the role of lay and professional patient navigators in Canada. Issue 4 (October 2020) - Reid, Amy E; Doucet, Shelley; Luke, Alison
Objectives: To explore the roles of patient navigators in different settings and situations for various patient populations and to understand the rationale for implementing lay and professional models of patient navigation in a Canadian context. Methods: A qualitative descriptive design was applied, using interviews with 10 patient navigators from eight Canadian provinces, and Braun and Clarke's six phases of thematic analysis to guide the analysis of interview transcripts. Results: Findings indicate that a patient navigator's personality and experience (personal and work-related) may be more important than their specific designation (i.e. lay or professional). Conclusions: Lay and professional navigators in Canada appear to be well suited to provide navigational services across populations. This study has the potential to inform future research, policy, and the delivery of navigation programmes in Canada.